The continuing effects of the COVID-19 pandemic on the autistic adult community in Aotearoa, New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Public Health, Massey University, New Zealand - Bramwell, Natasha Anne (Massey University, 2024)
The restrictions and disruptions that were caused by the COVID-19 pandemic in 2020-2022 have affected the mental health of many within the global community. Among these is the autistic community, who experience the world from a different point of view, and who are more susceptible to mental health issues such as anxiety and depression. The continuing disruption to routines, and access to dependable social constructs, rhythms, and rituals that autistic people rely on may have created further distress and exacerbated mental health issues. This research will investigate the lived experiences of autistic adults and how their day-to-day life experiences have changed since the pandemic. The qualitative methodology of phenomenology using thematic analysis through the lens of the social model of disability was applied to enable focus on what people experienced and felt during and following the pandemic. Purposive sampling and convenience sampling were adopted to recruit potential participants. There were 6 participants recruited and interviewed. The findings of the study revealed six key themes: 1) adjustments in social activity, 2) increased barriers to mental health support, 3) changes to community connections, 4) diminished overall well-being post-pandemic, and 5) changes to anxiety levels. The sixth and final theme peer-to peer advice, this theme incorporated suggestions for other autistic persons from participants. Disability support and health services have failed to keep up with the ongoing needs of the autistic adult community in New Zealand at a time when it was most needed. This study recommends striving for an increase in the understanding of autistic adult diagnoses in conjunction with improvements to autistic adult care. The service workers and health professionals require the ability to significantly expand their skills and knowledge of autism to provide better health outcomes, especially in times of disaster. Such expansions would require funding support driven by policy change.
Keywords: 420318 People with disability; 420602 Health equity